Implementation Degree of Quality Standards in the Special Education Program at Al-Balqa Applied University from the perspective of Faculty Members - Obaid Abdlekarim Al-Sabayleh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aimed to determine the implementation degree of quality standards in the special education program at Al-Balqa Applied University. Methods: The descriptive strategy was applied. A random cluster sample of 56 faculty members from Balqa Applied University made up the study sample. The Jordanian Universities Accreditation and Quality Assurance Authority's Manual of Jordanian Quality Assurance Standards for the Educational Sciences Program served as the foundation for the creation of the instrument. Results: According to the indicators of the standards for the three aspects of the standards, the study found that Al-Balqa Applied University's special education program applied quality standards to a high degree. However, the findings also revealed weaknesses in the policies that govern student transfer, a strained relationship between faculty members and library and database staff, and the absence of a more thorough, in-depth analysis. The demographics of faculty members' gender and academic rank are linked to how strictly quality standards are applied in Balqa Applied University's special education program. Conclusions: The study suggested updating academic materials for special education programs to achieve depth and current practices in special education, introducing periodic assessment procedures of special education programs, developing appropriate policies for students transferring from other academic programs, and strengthening the communication channel and relationship context among special education program's faculty members and workers in library and databases.